Photoreactivity of Imazethapyr Herbicide in the Presence of Suwannee River Fulvic Acids - Barkani, Hasnaa; Harir, Mourad; El-Azzouzi, Mohammed; El-Hourch, Abderahim; Mountacer, Hafida; Zrineh Ali Assabbanne, Abdellah; Ait lchou, Yaya; Chovelon, Jean-Marc (Asian Journal of Chemistry, 2010)
In the present work, the photoreactivity of imazethapyr herbicide in water in the presence of Suwannee river fulvic acids is reported.